Renal pathology-related factors in non-nephrotic-range proteinuria of lupus nephritis patients - LIU Ting-ting; YANG Yi; DAI Wei; LI Yue-qiang; HAN Min; HE Xiao-feng; GE Shu-wang; XU Gang (Linchuang shenzangbing zazhi)
Objective To explore the renal pathology-related factors of non-nephrotic-range proteinuria of biopsy-proven lupus nephritis( LN) patients and their prognosis. Methods We prospectively observed non-nephrotic-range proteinuria patients with biopsy-proven LN in Tongji Hospital affiliated to Tongji Medical College,Huazhong University of Science and Technology between Jan. 1,2004 and July 31,2018. All related baseline clinical data were recorded and regular follow-up was performed. The pathological sections of all patients were re-read and scored according to uniform criteria.According to the severity of renal pathology,the patients were divided into two groups: mild pathologic damage group and severe pathologic damage group. Log-rank test was used to compare the difference of remission rate between the mild pathologic damage group and severe pathologic damage group. Logistic regression equation was used to analyze the renal pathology-related risk factors. Results Ninety-five non-major proteinuria LN patients( female: 83. 2%,mean age: 32. 4 years) were enrolled,including79 follow-ups. There were 43 cases of mild renal pathologic damage group and 52 cases of severe renal pathologic damage group. Hemoglobin and serum IgA levels were significantly higher in mild pathologic group than in severe pathologic damage group( P < 0. 05). The follow-up results showed that the cumulative complete remission rate in the mild pathologic damage group was significantly higher than that in the severe pathologic damage group( P < 0. 05). Multivariate logistic regression results indicated age( OR = 1. 219,95% CI: 1. 043 to 1. 425,P < 0. 05),SLEDAI-2 K score( OR = 1. 202,95% CI: 1. 025 to 1. 411,P < 0. 05),initial proteinuria( OR = 3. 793,95% CI: 1. 058 to 1. 595,P < 0. 05),and serum IgA levels( OR = 0. 222,95% CI: 0. 063 to 0. 781,P < 0. 05) were independent renal pathology-related risk factors. Conclusions Older,high SLEDAI-2 K scores,high initial proteinuria and low serum IgA levels may be associated with severe renal pathologic damage in patients with non-nephrotic-range proteinuria LN.